1985
DOI: 10.1159/000180065
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Responses to Sleep, Insulin Hypoglycaemia and Arginine Infusion

Abstract: This study compares the peak serum growth hormone (GH) concentration during slow wave sleep with the serum GH responses to insulin-induced hypoglycaemia and intravenous arginine infusion in 23 children referred because of short stature (20) or precocious puberty (3). Peak serum GH concentration during sleep correlated significantly with peak GH response to insulin hypoglycaemia (r = 0.64, p < 0.01) and arginine infusion (r = 0.57, p < 0.01). 3 children had subnormal ( < 15 mU/1) peak serum GH concentrations du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…It is well known that ITT results in higher peak GH responses compared to most other classic tests ( Ward & Savage, 1985; Tapanainen et al ., 1988 ; Rasmussen et al ., 1995 ). It has also been demonstrated that the specificity is poor for the Arg test in adults ( Vahl et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ITT results in higher peak GH responses compared to most other classic tests ( Ward & Savage, 1985; Tapanainen et al ., 1988 ; Rasmussen et al ., 1995 ). It has also been demonstrated that the specificity is poor for the Arg test in adults ( Vahl et al ., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, spontaneous GH secre¬ tory episodes do occur in children with various pubertal stages (Greenwood et al, 1964, Finkelstein et al, 1972, Miller et al, 1982. They are present both during the night and waking hours (Hunter & Rigai, 1966, Takahashi et al, 1968, Honda et al, 1969, Parker et al, 1969, Miller et al, 1982, Minuto et al, 1982, Spiliotis et al, 1984, Sanz & Rochiccioli, 1985, Ward & Savage, 1985, Garnier et al, 1985, and daytime pulsatile GH secretory episodes have been clearly documented in prepubertal children. As shown by Miller et al (1982) and by Spiliotis et al (1984), these episodes are more frequent between 08.30 and 09.30 as well as around lunch time, although no clear relationship to meals could be established.…”
Section: Discussionmentioning
confidence: 99%